Régimen europeo de las ayudas públicas en tiempos del COVID 19 - Berenguer Fuster, Luis (2022)
In the context of the European Union, the competition policy ensures that the single market is maintained in order to guarantee the principles that characterise it. In terms of state aid, this policy means preventing Member States from granting aid to companies that would put them at an advantage over their competitors. Thus, Article 107 TFEU contains a general prohibition of state aid from which it is also possible to establish exceptions. Given the situation generated by COVID-19, the European Commission has been forced to make the European regime established for state aid more flexible on the basis of the possible exceptions with the aim of facilitating economic recovery in the Member States and, therefore, in the European Union. To this end, the European Commission has developed a “Temporary Framework for State aid measures to support the economy in the current COVID-19 outbreak”, which has been subject to successive modifications and extensions.